Intrapersonal and interpersonal processes of social exclusion - Kawamoto, Taishi; Ura, Mitsuhiro; Nittono, Hiroshi (Frontiers in Neuroscience, 2015)
People have a fundamental need to belong with others. Social exclusion impairs this need and has various effects on cognition, affect, and the behavior of excluded individuals. We have previously reported that activity in the dorsal anterior cingulate cortex (dACC) and right ventrolateral prefrontal cortex (rVLPFC) could be a neurocognitive index of social exclusion (Kawamoto et al., 2012, Frontiers in Evolutionary Neuroscience, 4, 11). In this article, we provide an integrative framework for understanding occurrences during and after social exclusion, by reviewing neuroimaging, electrophysiological, and behavioral studies of dACC and rVLPFC, within the framework of intrapersonal and interpersonal processes of social exclusion. As a result, we have indicated directions for future studies to further clarify the phenomenon of social exclusion from the following perspectives: (1) constructional elements of social exclusion, (2) detection sensitivity and interpretation bias in social exclusion, (3) development of new methods to assess the reactivity to social exclusion and (4) sources of social exclusion.